2018
DOI: 10.1016/s2468-2667(18)30044-6
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of take-home opioid antagonist kits during a synthetic opioid epidemic in British Columbia, Canada: a modelling study

Abstract: Canadian Institutes of Health Research Partnerships for Health Systems Improvement programme (grant 318068) and Natural Science and Engineering Research Council of Canada (grant 04611).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
67
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 20 publications
2
67
1
Order By: Relevance
“…Understanding correlates of take-home naloxone distribution and access is crucial for planning and targeting services aimed at curbing opioid overdoses. While analyses from the BCCDC shows that the BC THN program, combined with other harm reduction interventions, has averted thousands of opioid overdose deaths [20,21], there is still relatively little data in the published literature examining community reach and barriers to access of naloxone distribution programs in Canada. Furthermore, preliminary evidence from the BC Coroners Service suggests a spike in drug toxicity deaths corresponding with COVID-19 physical distancing measures and changes to the illicit drug supply; the Coroners Service reported a 130% increase in drug toxicity deaths in June 2020 compared to June 2019 [22].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding correlates of take-home naloxone distribution and access is crucial for planning and targeting services aimed at curbing opioid overdoses. While analyses from the BCCDC shows that the BC THN program, combined with other harm reduction interventions, has averted thousands of opioid overdose deaths [20,21], there is still relatively little data in the published literature examining community reach and barriers to access of naloxone distribution programs in Canada. Furthermore, preliminary evidence from the BC Coroners Service suggests a spike in drug toxicity deaths corresponding with COVID-19 physical distancing measures and changes to the illicit drug supply; the Coroners Service reported a 130% increase in drug toxicity deaths in June 2020 compared to June 2019 [22].…”
Section: Introductionmentioning
confidence: 99%
“…Amid intersecting crises of homelessness and climbing overdose rates, Vancouver continues to be recognized as an international leader in the rapid implementation of numerous interventions to reduce drug-related harms. In the downtown core, services such as needle distribution programs, supervised injection facilities and overdose prevention sites, the widespread distribution of take-home naloxone kits and the availability of opioid agonist therapies (OAT; e.g., methadone, buprenorphine/naloxone) have been paramount in reducing drug-related harms [ 5 , 12 , 13 ]. Across Greater Vancouver, various public health stakeholders are currently expanding efforts to create a comprehensive substance use care system for vulnerable adolescents and young adults that spans acute and community healthcare settings, including clinics, hospitals, and residential detox, treatment and recovery settings.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Michael Irvine and colleagues 4 provide new evidence on the importance of the provision of THN overdose prevention kits and their use specifically during an ongoing epidemic among people who use illicit synthetic opioids. By use of modelling techniques, the authors have estimated the number of deaths averted by THN and shown how this number could be further increased with earlier provision.…”
Section: Take-home Naloxone: While Good It Is Far From Good Enoughmentioning
confidence: 99%
“…Progress is being made, and wider, evidencedbased health and social responses and interventions to drug problems are emerging. 7 The current work by Irvine and colleagues 4 is an example of how wider disciplines of statistical and mathematical modelling can contribute to debate and evidence on the topic of substance misuse. Although the challenges within substance misuse research are daunting, the rewards of evidence-based scientific results can be life changing for people who use drugs, their families, and their communities.…”
Section: Take-home Naloxone: While Good It Is Far From Good Enoughmentioning
confidence: 99%